A High‐Performance Composite Electrode for Vanadium Redox Flow Batteries. Issue 18 (12th May 2017) - Deng, Qi; Huang, Peng; Zhou, Wen‐Xin; Ma, Qiang; Zhou, Nan; Xie, Hao; Ling, Wei; Zhou, Chun‐Jiao; Yin, Ya‐Xia; Wu, Xiong‐Wei; Lu, Xiang‐Yang; Guo, Yu‐Guo
Abstract : A composite electrode composed of reduced graphene oxide‐graphite felt (rGO‐GF) with excellent electrocatalytic redox reversibility toward V 2+ /V 3+ and VO 2+ /VO2 + redox couples in vanadium batteries was fabricated by a facile hydrothermal method. Compared with the pristine graphite felt (GF) electrode, the rGO‐GF composite electrode possesses abundant oxygen functional groups, high electron conductivity, and outstanding stability. Its corresponding energy efficiency and discharge capacity are significantly increased by 20% and 300%, respectively, at a high current density of 150 mA cm −2 . Moreover, a discharge capacity of 20 A h L −1 is obtained with a higher voltage efficiency (74.5%) and energy efficiency (72.0%), even at a large current density of 200 mA cm −2 . The prepared rGO‐GF composite electrode holds great promise as a high‐performance electrode for vanadium redox flow battery (VRFB). Abstract : A reduced graphene oxide‐graphene felt electrode with excellent electrocatalytic redox reversibility toward V 2+ /V 3+ and VO 2+ /VO2 + redox couples in vanadium batteries is fabricated using a facile hydrothermal method. The composite electrode possesses abundant oxygen functional groups, high electron conductivity, and outstanding stability. Moreover, a discharge capacity of 20 A h L −1 is obtained with a high voltage efficiency (74.5%) and energy efficiency (72.0%), even at a large current density of 200 mA cm −2 .